2007
DOI: 10.1177/0020764006074522
|View full text |Cite
|
Sign up to set email alerts
|

A Western Australian Survey On Public Attitudes Toward and Knowledge of Electroconvulsive Therapy

Abstract: The findings suggest that clinicians should ensure that individuals recommended for ECT are knowledgeable about basic ECT processes and implications in order to ensure their full informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
2
21
1
1
Order By: Relevance
“…A qualitative study, exploring the decision making toward ECT in older adults, identified stigma as a major hurdle in electing to ECT (Amazon, McNeely, Lehr, & Marquardt, ), but to our knowledge, except from general studies of attitudes toward ECT (Aoki et al., ), no studies have thoroughly explored the stigma related to ECT. Addressing and incorporating both individual and structural factors in the study designs of stigma is recommended (Corrigan & Shapiro, ; Pescosolido, Martin, Lang, & Olafsdottir, ), but to date, research does not specifically document the voices of professional experts, such as clinicians, politicians, or journalists, despite the fact that legislation and the media are often mentioned as important determining factors in attitudes toward ECT (Dowman et al., ; Fink, ; Teh, Helmes, & Drake, ). As such, the purpose of this study was to explore the experiences and attitudes of former recipients of ECT and of experts professionally involved with ECT to identify processes of stigmatization and potential anti‐stigma strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study, exploring the decision making toward ECT in older adults, identified stigma as a major hurdle in electing to ECT (Amazon, McNeely, Lehr, & Marquardt, ), but to our knowledge, except from general studies of attitudes toward ECT (Aoki et al., ), no studies have thoroughly explored the stigma related to ECT. Addressing and incorporating both individual and structural factors in the study designs of stigma is recommended (Corrigan & Shapiro, ; Pescosolido, Martin, Lang, & Olafsdottir, ), but to date, research does not specifically document the voices of professional experts, such as clinicians, politicians, or journalists, despite the fact that legislation and the media are often mentioned as important determining factors in attitudes toward ECT (Dowman et al., ; Fink, ; Teh, Helmes, & Drake, ). As such, the purpose of this study was to explore the experiences and attitudes of former recipients of ECT and of experts professionally involved with ECT to identify processes of stigmatization and potential anti‐stigma strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that ECT is an efficacious treatment, with adverse ef-fects mostly limited to transient cognitive impairment (1,2). Despite this favorable side-effect profile, the public at large tends to perceive ECT as potentially harmful (1)(2)(3)(4)(5). In one study, younger age, cultural factors (e.g., language), and exposure to individuals with mental illness were predictors of less favorable perceptions (2).…”
Section: Discussionmentioning
confidence: 99%
“…Public opinion seems to continue to perceive ECT unfavorably, especially as information about its safety is not well dispersed. A public opinion survey conducted by the department of Justice in Western Australia found that most of the respondents who indicated they had some knowledge about the main aspects of ECT opposed its use in children [109]. However, the respondents were not particularly involved in the ECT process and were not necessarily exposed to patients receiving ECT.…”
Section: Public Opinion and Attitudesmentioning
confidence: 99%